If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(-0.5 + 0.25y) + y = 3 (-0.5 * -8 + 0.25y * -8) + y = 3 (4 + -2y) + y = 3 Combine like terms: -2y + y = -1y 4 + -1y = 3 Solving 4 + -1y = 3 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1y = 3 + -4 Combine like terms: 4 + -4 = 0 0 + -1y = 3 + -4 -1y = 3 + -4 Combine like terms: 3 + -4 = -1 -1y = -1 Divide each side by '-1'. y = 1 Simplifying y = 1
| 2(-4.2+y)-3y=-9 | | 4(-3+2y)-3y=8 | | 14x+6y=180 | | 2x^2-17x+128=0 | | 11-4x=-7x+5 | | 5/8(X-6)=2+4X | | 5x^2-16x-12=0 | | 47.5=9.5 | | 9.5=47.5 | | 81-9= | | -76=26m | | -24(3)-4= | | 2*x^2-7*x-15=0 | | 5x^2-18x-21=0 | | y+7-6= | | 21-3(4-1)= | | 324(1-x)=36 | | 18.8=2*3.14*r | | -7a^2b+2ab^2= | | 210=4*9*5+2*5*H | | x^2-11x+82=0 | | 2x+3=5x-5/3 | | y+x=r | | 2(x+9)=3(x-3) | | 78=2x-12 | | 9=y+c | | 20+b=a | | 4/3=x+2/8 | | 5w+6=16w-3w+54 | | 9y-14=6y-2 | | -3w+11=-8w+51 | | y=7x^2-4x |